O educar pela pesquisa como proposta didática nas aulas de educação física do ensino médio integrado - Deus, Gabriela Brum de (2021)
Physical Education at school is often limited to just repeating motor gestures imposed by the teacher and considering the student as a simple passive agent of knowledge, when he should allow him to become an active and reflective subject of his own teaching and learning process. In high school, the challenge is greater, as students in this age group are increasingly less active, which is a concern for health, as sedentary teenagers tend to become sedentary adults. In Integrated Secondary Education (EMI), a teaching modality of the Federal Institutes that articulates the basic knowledge of secondary level with professional and technical skills, these factors are accentuated, due to the high workload and because most students only exercise during school. Physical Education class, which takes place only once a week. In view of this, as a way of reframing this scenario and contributing to the integral training of students, this master's research aimed to elaborate and analyze the application of a didactic proposal based on Educating through Research (EPP), to develop the theme of health in Physical Education classes from Integrated High School. It is an action research, with a qualitative and quantitative approach, which was divided into two moments. Initially, a survey of the physical fitness indexes for health and motor performance of IFFar students - São Vicente do Sul campus was carried out over a period of four years (2016-2019), and later, a didactic proposal was developed and applied with students. third year students, challenging them to train at least three times a week in order to improve their physical fitness indexes. The EPP was chosen because this proposal is based on reconstructive questioning and encourages students to be active, participative, productive and reconstructive. The PROESP/BR battery of tests (to obtain the students' physical fitness level) and the analysis of the posts in the closed group of the social network Facebook and the reports in the presentation of the seminar (to evaluate the didactic proposal) were used as research instruments. To analyze the collected data, statistical analysis and content analysis were used. When analyzing the results, EMI students showed unsatisfactory rates in physical fitness for health and motor performance and in 2019 the lowest rates were shown, showing that students are reducing the practice of physical activity. Regarding the didactic proposal, it was observed that it increased the indexes of physical fitness for health and motor performance and the students reflected on their daily habits and daily food. In addition, it allowed active participation, the development of reconstructive and critical questioning in relation to health and the autonomy and confidence to plan, organize, adapt and define training locations. Thus, it is inferred that a didactic proposal contextualized and based on the EPP can contribute to the health and comprehensive training of EMI students.